Benefits of Online and Offline Resources for Teaching English and Norwegian as Foreign Languages in a Post-Pandemic Context - Diana Lățug; Adina-Virginia Lung (Linguaculture)
The study seeks to evaluate how teaching a foreign language (English, Norwegian, or both) has been influenced by the availability of online and offline resources in the post-pandemic context. It also highlights the adaptability of both educators and students alike in using such available resources and emphasizes the process of incorporating gamification in teaching a foreign language. Moreover, it is an attempt to point out to what extent such resources and practices are beneficial to students and helpful for educators. The focus groups are comprised of university students learning Norwegian as a foreign language as well as  pre-university level students of English as a second language.